2019
DOI: 10.1007/s00217-019-03262-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profile of phenolic acids and antioxidant activity of wheat grain exposed to stress

Abstract: In the case of biotic and abiotic stresses, natural defence mechanisms are triggered in plants. The mechanisms are based mainly on enzymatic or non-enzymatic intracellular reactions. Changes in the quantitative profile of 12 phenolic acids, total bound phenolic acids, total free phenolic acids and antioxidant activity in grain of 23 winter wheat genotypes exposed to stress (artificial inoculation with spores of fungi from the genus Fusarium or chemical protection) were analysed. Concentrations of ergosterol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…The influence of the variety on the ferulic acid content is confirmed by numerous studies; however, differences in the examined content of this acid are observed [60][61][62]. Stuper-Szablewska et al [21] showed that the average content of ferulic acid under control conditions was 844 mg/kg, 780 mg/kg, and 771 mg/kg in the years of the study. After inoculation, these values increased to 2248 mg/kg, 2574 mg/kg, and 3145 mg/kg, respectively [21].…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…The influence of the variety on the ferulic acid content is confirmed by numerous studies; however, differences in the examined content of this acid are observed [60][61][62]. Stuper-Szablewska et al [21] showed that the average content of ferulic acid under control conditions was 844 mg/kg, 780 mg/kg, and 771 mg/kg in the years of the study. After inoculation, these values increased to 2248 mg/kg, 2574 mg/kg, and 3145 mg/kg, respectively [21].…”
Section: Discussionmentioning
confidence: 78%
“…Stuper-Szablewska et al [21] showed that the average content of ferulic acid under control conditions was 844 mg/kg, 780 mg/kg, and 771 mg/kg in the years of the study. After inoculation, these values increased to 2248 mg/kg, 2574 mg/kg, and 3145 mg/kg, respectively [21].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations